Intellect, inter(dis)course and identity: the production and resistance of masculinity in graduate education - Wolgemuth, Jennifer R., author; Cobb, R. Brian, advisor; Bubar, Roe, committee member; Harbour, Clifford, committee member; Pamphilon, Barbara, committee member (Colorado State University. Libraries, 2007)
The purpose of this dissertation was to examine how male graduate students make sense of what it means to be a man in order to illuminate potential links between higher education and the production of male subjects. These links were conceptualized in three foci: Theory - as (hegemonic) masculine domination in higher education, Practice - as academic discourses taken up to construct gender and masculinity, and Process - as engaging in critical reflection (Brookfield, 1987, 1998) and critical resistance (Hoy, 2005) of the proscriptives of normative masculinity. Designed as a narrative inquiry and using an interview method called an inquiry of discomfort (Wolgemuth & Donohue, 2006), this study engaged 5 male graduate students from counseling, social economy, computer science, media analysis, and social science disciplines in conversations about masculinity and their experiences as graduate students. These conversations occurred across a semester and were captured in five to seven audio recorded interviews. The interviews were analyzed in three stages, likened to the process of gathering materials to paint: deconstruction-trace analysis (pencils), argument analysis (brushes), and resistance analysis (paint). The analyses produced subjectivity portraits, write-ups of the participants' interviews, describing the subjects they constructed, the hegemonic and ideal man, and their "Others", and how they affected critical resistance (Hoy, 2005). Guided by the work of Foucault and Butler, the findings were discussed in terms of the dissertation's three foci. Theoretically, a new understanding of male dominance was proposed, one that redefined male dominance as negotiated. In practice, academic discourses (sociobiological, humanist, social science, (pro)feminist, and postmodern) were found to be taken-up to construct masculinity and make sense of the gender order. And the process of engaging in critical reflection was found not to necessarily entail critical resistance (Hoy, 2005). The three foci were woven together in five "lessons learned" that inform supervisors' work with male graduate students to foster critical resistance. The lessons were: (a) Emphasize male dominance as negotiated; (b) Identify and challenge gender implications of academic discourses; (c) Identify and challenge the gender implications of the "ideal" graduate student; (d) Ask questions that maintain reflection as a critical activity and (e) Value ambiguity and the male graduate student as a "subject-in-progress."
Keywords: educational sociology; women's studies; gender studies; higher education